Pengaruh Penerapan Pendekatan Variasi Terhadap Hasil Belajar Tortor Hata Sopisik Pada Siswa Kelas IV SD Negeri 132403 Tanjung Balai - Indah Gustianingsih Siregar (Universitas Negeri Medan, 2017)
This study aims to determine the effect of variations in the application of the learning outcomes approach Tortor Hata Sopisik fourth grade of SD Negeri 132403 Tanjungbalai. In this discussion the use of theories related to the topic of research is the theory of learning, learning outcomes, and approaches variation. The method used in this research is quantitative research methods. The sample in this study amounted to 34 students who are fourth grade students of SD Negeri 132403 Tanjungbalai. Instruments used in this research is to test the practice of dance. From the data acquisition is known that the learning outcomes tortor Hata Sopisik Elementary School fourth grade students 132 403 Tanjungbalai before applying the variation approach into the category of less with the average value and standard deviation = 58.76 = 6.58. While the study Tortor Hata Sopisik fourth grade of SD Negeri 132403 Tanjungbalai after applying a variation approach fit into both categories with the average value and standard deviation = 76.94 = 8.50. Furthermore, the second data test result above the normal distribution. From the homogeneity test can be found in this sample came from a homogenous population. After tests of normality and homogeneity, obtained t0 at 9.722. After t0 is known, then consulted with the table t the significance level of 5% with df = N-1 = 34-1 = 33 gained significance level of 5% = 1.692. Because t0 obtained greater than ttable namely 9.722> 1.692, then the hypothesis is accepted. It can be concluded that there are significant variations in the application of the learning outcomes approach Tortor Hata Sopisik fourth grade of SD Negeri 132403 Tanjungbalai. Keywords: Learning, Learning Outcomes, Approach Variation.